Manajemen Konflik Interpersonal (Studi Kasus pada CV Cyber Karya Nusantara Surabaya) - Lizha Khusmah Sakha Wijaya; Jorgy, Endin; Latif, Moh Daniyal (Jurnal Nusa Manajemen, 2024)
Interpersonal conflict is something that cannot be avoided in organizations, one of which is at CV Cyber Karya Nusantara Surabaya. The aim of this research is to find out a picture of interpersonal conflict management at CV Cyber Karya Nusantara Surabaya. Descriptive qualitative methods were used in this research with data collection techniques obtained from interviews and observations. The results of this research indicate that interpersonal conflict at CV Cyber Karya Nusantara Surabaya is caused by the lack of effective communication between team members and the ongoing organizational transformation. The conflict resolution or conflict management used is to use accommodation, integration and avoidance styles. The accommodation and integration style is used by the chairman or superior to resolve interpersonal conflicts experienced by employees, while the avoidance style is used by employees who experience interpersonal conflicts at CV Cyber Karya Nusantara Surabaya.